X+(2x+1)+(3x+2)=

Simple and best practice solution for X+(2x+1)+(3x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(2x+1)+(3x+2)= equation:


Simplifying
X + (2x + 1) + (3x + 2) = 0

Reorder the terms:
X + (1 + 2x) + (3x + 2) = 0

Remove parenthesis around (1 + 2x)
X + 1 + 2x + (3x + 2) = 0

Reorder the terms:
X + 1 + 2x + (2 + 3x) = 0

Remove parenthesis around (2 + 3x)
X + 1 + 2x + 2 + 3x = 0

Reorder the terms:
1 + 2 + X + 2x + 3x = 0

Combine like terms: 1 + 2 = 3
3 + X + 2x + 3x = 0

Combine like terms: 2x + 3x = 5x
3 + X + 5x = 0

Solving
3 + X + 5x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + X + -3 + 5x = 0 + -3

Reorder the terms:
3 + -3 + X + 5x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + X + 5x = 0 + -3
X + 5x = 0 + -3

Combine like terms: 0 + -3 = -3
X + 5x = -3

Add '-5x' to each side of the equation.
X + 5x + -5x = -3 + -5x

Combine like terms: 5x + -5x = 0
X + 0 = -3 + -5x
X = -3 + -5x

Simplifying
X = -3 + -5x

See similar equations:

| 85=25-4x | | x+3x+2x^2=840 | | 8/x=-20 | | a-24=-15 | | (a+c-e)f=(b+1000-c-f)e | | 0.125=g-4.4 | | 2x-1/5=5x-1/4 | | 16-r^2=0 | | 3x-2=-2(x+11) | | 15-6m+6m= | | 54+55=x+74 | | 29x-15= | | 25x-2=23x+2 | | 36x+128= | | 7p^2+24p+16=0 | | Cos(65)=10/x | | 43x+135= | | 8+3(1x-1)= | | 4x^2-4x+4=14 | | -2+6+2x=28 | | 2u^2+u-10=0 | | 1/3(3.14)(225)(20) | | 6w-19w= | | 8p+5=7p | | p^2-2p-(1/8)=0 | | 5c/=35 | | 3c+7=4 | | -7(1+2x)=-105 | | 7y-11+3(y+1)=9y-1 | | 5/7x= | | b=90+(15+7) | | 2+1n=16-6n |

Equations solver categories